2015
DOI: 10.1016/j.bbalip.2015.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Modification of sphingolipid metabolism by tamoxifen and N-desmethyltamoxifen in acute myelogenous leukemia—Impact on enzyme activity and response to cytotoxics

Abstract: The triphenylethylene antiestrogen, tamoxifen, can be an effective inhibitor of sphingolipid metabolism. This off-target activity makes tamoxifen an interesting ancillary for boosting the apoptosis-inducing properties of ceramide, a sphingolipid with valuable tumor censoring activity. Here we show for the first time that tamoxifen and metabolite, N –desmethyltamoxifen (DMT) block ceramide glycosylation and inhibit ceramide hydrolysis (by acid ceramidase, AC) in human acute myelogenous leukemia (AML) cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…Both tamoxifen and its metabolite N- desmethyltamoxifen specifically reduce ceramide glycosylation and inhibit acid ceramidase independent of known anti-estrogen mechanisms. Co-treatment with tamoxifen and exogenous ceramide or a ceramide-generating drug induced synergistic apoptosis in AML cells 77 .…”
Section: Ac Inhibitorsmentioning
confidence: 98%
“…Both tamoxifen and its metabolite N- desmethyltamoxifen specifically reduce ceramide glycosylation and inhibit acid ceramidase independent of known anti-estrogen mechanisms. Co-treatment with tamoxifen and exogenous ceramide or a ceramide-generating drug induced synergistic apoptosis in AML cells 77 .…”
Section: Ac Inhibitorsmentioning
confidence: 98%
“…Apropos in this context, tamoxifen can suppress ceramide metabolism via glycosylation (13) and inhibit hydrolysis (14), thus reducing S1-P formation (15). Therefore, when used in combination with a cell-deliverable ceramide, such as C6-ceramide, or ceramide-generating drugs, beneficial actions from a therapeutic standpoint can be realized.…”
Section: Mitochondrial Respirationmentioning
confidence: 99%
“…In earlier work in HL-60/VCR cells, we demonstrated that tamoxifen enhanced the cytotoxicity of fenretinide, a ceramide-generating retinoid (16), and C6-ceramide; however, mechanisms supporting this enhancement had not been elucidated (15). Herein, we demonstrate that the mechanisms promoting C6-ceramide-tamoxifen cytotoxicity in AML cells encompass a reduction in mitochondrial membrane potential, inhibition of complex I respiration, generation of reactive oxygen species (ROS), reduced glycolytic capacity, and decreases in ATP.…”
Section: Mitochondrial Respirationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to inhibition of ceramide glycosylation [21], tamoxifen also exhibits a number of estrogen receptor-independent actions, including circumvention of multidrug resistance, downregulation of survivin, inhibition of Acyl-CoA: cholesterol acyl transferase (ACAT) [22], and downregulation of acid ceramidase [15]. The capacity to block ceramide glycosylation has made tamoxifen an object of myriad investigations into its use as an adjuvant with ceramide-centric therapies, including 4-HPR [23], short-chain ceramides [24], and short-chain ceramides in combination with paclitaxel [25]. Although tamoxifen is not a direct inhibitor of GCS, it limits intracellular production of GC by blocking GC transport into the Golgi, a process that requires Golgi-resident P-gp [22].…”
Section: Introductionmentioning
confidence: 99%